FACTORS CAUSING LOW STUDENT PARTICIPATION IN THE IMPLEMENTATION OF THE 2020 FKIP UNIVERSITY OF LAMPUNG STUDENT ELECTION (POLITICAL EDUCATION STUDIES IN HIGHER EDUCATION THROUGH STUDENT ORGANIZATIONS) - Amiza Rezika; Asep Mahpudz; Kokom Komalasari; Sapriya (SOSIOEDUKASI, 2025)
The purpose of this study is to find out what factors are the causes of low student participation in the implementation of FKIP Unila in 2020 and then compare which factors have the most significant influence. The method used in this study is a survey method with a quantitative approach. The subject in this study is a student of the Faculty of Teacher Training and Education, University of Lampung. The sample used in this study amounted to 98 respondents. The data collection technique in this study uses the main technique, namely questionnaire and uses supporting techniques, namely interviews. The data analysis in this study was using the frequency distribution of indicators and assisted by SPSS version 20. The results of the study show that the factors causing the low student participation in the implementation of the FKIP in 2020 are caused by two factors, namely internal factors and external factors. Internal factors show a percentage of 45.91% less influential, 50% quite influential and 4.08% influential. Meanwhile, external factors showed a percentage of 29.59% less influential, 46.93% quite influential and 23.46% influential. Thus, it can be concluded that significantly external factors are more significant in causing low student participation in the implementation of the 2020 FKIP Unila.